Effectiveness and feasibility of Narrative Exposure Therapy (NET) in patients with borderline personality disorder and posttraumatic stress disorder – a pilot study. Issue 1 (December 2016) - Steuwe, Carolin; Rullkötter, Nina; Ertl, Verena; Berg, Michaela; Neuner, Frank; Beblo, Thomas; Driessen, Martin
Abstract Background This pilot study focused on the feasibility and potential effectiveness of a protocol based on Narrative Exposure Therapy (NET) that was integrated into a standard inpatient program to treat patients with comorbid Borderline Personality Disorder (BPD) and Posttraumatic Stress Disorder (PTSD). Methods Eleven patients (1 male, 10 female) without previous stabilization periods or the absence of intentional self-injury received NET during a ten-week inpatient program. Patients were assessed again at post-treatment and a 12-month follow-up. Results Drop-out rates during treatment were low, with 90.9 % completing NET. Furthermore, acceptance of NET was high, with only one patient rejecting treatment. The program was safe because it did not lead to aggravations in symptom severity at either the post-treatment or 12-month follow-up. Additionally, the rate of self-harming behaviors throughout the treatment phase was low (18.2 %). In fact, treatment was associated with positive effects on PTSD and BPD symptom severity as well as secondary outcome measures, including depression, dissociation and quality of life. Conclusions The present study found that NET is feasible and safe in an inpatient setting for treating highly burdened patients with BPD and PTSD. There is also evidence for the potential effectiveness of NET in this highly burdened population. Trial registration ClinicalTrials.gov Identifier:NCT02517723 . Registered 6 January 2014.